Phenomenon of mask as medium in world cultural history - Kirillova, Natalia B. (Journal of the Belarusian State University. History, 2022)
The object of research is the phenomenon of the mask as a unique phenomenon of culture. The subject of analysis is the symbolism of the mask as a medium and a mythological code in different historical eras determined by certain socio-cultural trends. Having originated in primitive society, the mask has been developing throughout the history of human civilisation. In the study it was proved that one of the main social functions of the mask, which has arisen historically, is to be a medium, that is, an intermediary between man and society, the real and mythological worlds. Taking the genesis and evolution of the mask as a basis for the study, analysis of the interaction of the mask and myth-making in the history of ritual and theatrical culture, the authors proceed from the relevance of this problem in the context of the new social and cultural reality, including the pandemic, when the mask becomes a symbol of protection.
Keywords: mythological consciousness; cultural history; phenomenon of the mask; magic; mythological reality; ritua; myth